Larval development of the freshwater shrimp Atyaephyra desmarestii (Millet, 1831) sensu lato (Decapoda: Caridea: Atyidae) and morphological maturation from juveniles to adults - Anastasiadou, Chryssa; Ntakis, Alexandros; Leonardos, Ioannis D. (Zootaxa, 2011)
A complete serial of larval staging of Atyaephyra desmarestii (Millet, 1831) sensu lato from Louros River (north-western Greece) was obtained in the laboratory and described in detail. Thirty berried females were collected and transferred to an aquarium containing water and vegetation from the sampling site. The newly hatched larvae were transferred into small sterile aquaria and mass cultured. After each moult, several larvae were photographed and preserved with their exuviae. The reared larvae of A. desmarestii sensu lato passed through six zoeal stages and one megalopal stage. At the experimental conditions, the durations of each larval stage were as follows: three days for the 1 st larval stage; three to four days for 2 nd larval stage; six to eight days for 3 rd ; seven to nine days for 4 th ; nine to ten days for 5 th , 6 th and megalopal stages. All the obtained stages were described in detail. The larval morphological characters of the described material and the larvae specimens collected from natural populations were compared with the literature data on closely related species. Morphological description of the different phases for juveniles, immature, female and male mature individuals of A. desmarestii sensu lato are also presented in detail.